Pola Komunikasi Pemain Gim Daring Player Unknown Battle Ground Desa Kepuh Sukoharjo - Wijayakusuma, Guruh (Solidaritas, 2025)
This study aims to analyze the communication patterns of Player Unknown Battle Ground (PUBG) players in the Kepuh Village community, Sukoharjo. PUBG players in Kepuh Village, Sukoharjo communicate virtually when playing PUBG, before or after the game, even though they are not physically close to each other. Simple facial expressions and high-pitched intonations are non-verbal communication for PUBG players in Kepuh Village. Verbal and non-verbal interactions form multi-directional communication patterns by exchanging ideas dialogically. The passive communication style of PUBG players is formed in the behavior of 'silent' or choosing to only continue playing with their gadgets when blaming other players. Aggressive communication by mocking each other's playing style and methods, to the point of scaring their playmates. The most visible assertive communication style is when PUBG players in Kepuh Village play compactly with good coordination to be able to win the game. Keywords: PUBG Online Game, Communication Patterns, and Communication Style